Der Einfluß des CO2-Gehaltes der Bodenluft auf die Kalklösung - Gerstenhauer, Armin (ERDKUNDE, 1972)
The aim of the investigation was to estimate the extent to which limestone solution could be explained by the CO2 content of the soil atmosphere. For this purpose an experi ment was carried out in the Bergisches Land in which the soil atmosphere was sampled at 30 cm depth every five days with a probe which remained in the ground for the whole period, and the CO2 content was determined (using Drager’s multigas detector). Parallel to this, the relevant temperature was read from a mercury soil thermometer. In comparison to previous measurements it was thus possible to determine the typical annual pattern of CO2 content in the soil atmosphere in its dependence on the weather pattern. From the mass of the water seeping underground, that is, the water which would become effective in karst-morphological terms, and the CO2 content of the soil atmosphere, it was possible to calculate, with simplified threshold constraints, the amount of limestone likely to be dissolved. The calculations showed that the effects of CO2 variations in the soil on the rate of limestone solution were relatively minor and that the amount of effective karst-morphological water was decisive for the amount of limestone solution. These experiences indicate that, in the explanation of climate specific karst forms, no excessive significance should be attached to CO2 production in the soil atmosphere.